2012
DOI: 10.1590/s2237-93632012000100008
|View full text |Cite
|
Sign up to set email alerts
|

Anal fistula: results of surgical treatment in a consecutive series of patients

Abstract: Objectives:To evaluate the results of surgical treatment of patients with anal fistulas in a consecutive series of patients. Methods: A retrospective analytical study of a consecutive series of cases prospectively collected. The sample comprised 210 patients who underwent surgery; demographic data, signs and symptoms, intraoperative classification of the fistulas and healing time were analyzed. results: The median age was 38 years and 69.0% of the patients were male. The most frequent symptom was perianal orif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
0
10
0
2
Order By: Relevance
“…Seton has low rate or recurrence and was nil in the present study it causes minimal damage to the sphincter mechanism and is preferred in high fistulas (Table 1). 8,9 In this study, 66% of patients had low level of fistula-inano and another, 34% of patients had a high level of fistula-in-ano. A study done by Jethva et al, also observed that higher number of patients had fistula-in-ano of low level.…”
Section: Figure 1: Distribution Of the Patients According To Differenmentioning
confidence: 48%
“…Seton has low rate or recurrence and was nil in the present study it causes minimal damage to the sphincter mechanism and is preferred in high fistulas (Table 1). 8,9 In this study, 66% of patients had low level of fistula-inano and another, 34% of patients had a high level of fistula-in-ano. A study done by Jethva et al, also observed that higher number of patients had fistula-in-ano of low level.…”
Section: Figure 1: Distribution Of the Patients According To Differenmentioning
confidence: 48%
“…However, in this study male gender was dominant in both groups and overall mean age was 31+2.3 years. Similarly, Oliveira PG et al 9 reported that the patient's median age was 38 years with rage of 12 to 78 years and most of the cases 62.8% were observed with age group of 30 to 40 years. The predominant gender was male (69.0%), in a ratio of 2.2:1.…”
Section: Discussionmentioning
confidence: 80%
“…Fistula is an abnormal pathway that conveys two epithelized surfaces; if there should arise an occurrence, it associates the region anorectal to the skin. 8 This illness is highly prevalent among men and influenced primarily individuals in the age of 30 to 40 years and most commons symptoms of the inflammatory tumor are pain and purulent drainage. However, in this study male gender was dominant in both groups and overall mean age was 31+2.3 years.…”
Section: Discussionmentioning
confidence: 99%
“…Anal fistulas represent an essential aspect of colorectal practice, emerging as a distressing condition for patients and sometimes imposing a challenge upon surgeons. They have been classified into four significant types according to their relation to the anal sphincter complex, which include intersphincteric, transsphincteric, suprasphincteric and extrasphincteric ( 3 , 8 ). This classification is a means of helping to improve the management plan.…”
Section: Discussionmentioning
confidence: 99%
“…This classification is a means of helping to improve the management plan. Treatment strategies should incorporate a closure of the internal opening and an excision of the infected fistula tract with preservation of the sphincter complex ( 3 , 5 , 8 10 ).…”
Section: Discussionmentioning
confidence: 99%